Inefficient Markets: An introduction to behavioural finance - Shleifer Andrei (United states Oxford university press, 2000)
This book describes an alternative approach to the study of financial markets: behavioral finance. it presents and empirically evaluates models of such inefficient markets, builds a new theoretical and empirical foundation for the economic analysis of real-world markets.
Includes bibliographical references (198-210) and index.
nmn, 26/07/16
Loans
Keywords: Investments; Finance; Stocks-prices; Efficient market theory